Acute evaluation of conversational discourse skills in traumatic brain injury. (December 2014) - LeBlanc, Joanne; de Guise, Elaine; Champoux, Marie-Claude; Couturier, Céline; Lamoureux, Julie; Marcoux, Judith; Maleki, Mohammed; Feyz, Mitra
Abstract This study looked at performance on the conversational discourse checklist of the Protocole Montréal d'évaluation de la communication (D-MEC) in 195 adults with TBI of all severity hospitalized in a Level 1 Trauma Centre. To explore validity, results were compared to findings on tests of memory, mental flexibility, confrontation naming, semantic and letter category naming, verbal reasoning, and to scores on the Montreal Cognitive Assessment. The relationship to outcome as measured with the Disability Rating Scale (DRS), the Extended Glasgow Outcome Scale (GOS-E), length of stay, and discharge destinations was also determined. Patients with severe TBI performed significantly worse than mild and moderate groups (χ2KW2df = 24.435, p = .0001). The total D-MEC score correlated significantly with all cognitive and language measures (p < .05). It also had a significant moderate correlation with the DRS total score (r = −.6090, p < .0001) and the GOS-E score (r = .539, p < .0001), indicating that better performance on conversational discourse was associated with a lower disability rating and better global outcome. Finally, the total D-MEC score was significantly different between the discharge destination groups (F(3, 90) = 20.19, p < .0001). Thus, early identification of conversational discourse impairment in acute care post-TBI was possible with the D-MEC and could allow for early intervention in speech-language pathology.